MOTIVES FOR USING THE @NGEDRAKOR_YUKK TIKTOK ACCOUNT AS A KOREAN DRAMA STREAMING PLATFORM - Finanda, Siska Virgina; Sudrajat, Anazia; Amalia, Tria; Nurfalah, Farida; Wihayati, Welly (Ridwan Institute, 2024)
The Korean Wave (Hallyu) phenomenon is the impact of the presence of the internet, one of which is Korean drama. The great interest in Korean dramas has led to the formation of the K-Drama Lovers community. Korean dramas can be accessed by viewers via legal streaming platforms. However, this platform is starting to be challenged by the existence of illegal platforms via social media, such as TikTok. The distribution of Korean dramas via the TikTok account @ngedrakor_yukk is done by uploading parts of Korean drama episodes in a row in short video format. The research aims to understand the motives for using the TikTok account @ngedrakor_yukk as a Korean drama streaming platform through the Uses and Gratifications Theory approach. The research subjects were followers of the TikTok account @ngedrakor_yukk. The research used qualitative methods with data collection techniques through observation, interviews and literature studies. The research results show that the motive for watching Korean dramas on the TikTok account @ngedrakor_yukk is driven by four motives, most followers use the information motive to look for recommendations and ratings of Korean dramas on the TikTok account @ngedrakor_yukk, some followers use the personal identity motive to seek inspiration from the drama's moral values Korea on the TikTok account @ngedrakor_yukk, some followers use social integrity motives to interact with fellow Korean drama viewers on TikTok, and most informants use entertainment motives to seek enjoyment from entertaining Korean drama content accompanied by attractive TikTok features.